Alex Potts in conversation with Lily Cox-Richard "The Stand (Possessing Powers)" - Potts, Alex 1943-; Cox-Richard, Lily 1979- (2016)
Alex Potts interviews sculptor Lily Cox-Richard in relation to her recent project The Stand (Possessing Powers). Each of these plaster sculptures takes a major work by Hiram Powers, such as The Greek Slave, as its starting point, removing the naked female figure for which Powers is best known and isolating and refashioning the stand—the part most people ignore. The transformation effected by such a radical displacement of the figure and refashioning of the stand as an autonomous sculpture paradoxically draws attention to a significance inherent in Powers’s work which might otherwise be ignored. Cox-Richard’s project raises important questions about how Powers’s work can still speak to a contemporary artist for whom the core values informing his conception of sculpture are in many respects radically alien.
Keywords: Powers, Hiram -- 1805-1873 -- Griechische Sklavin; Cox-Richard, Lily -- 1979-; Rezeption